Simon Fraser University - Earthgazing VR experience to help astronauts cope with loneliness (Education News Canada, 2021)
Research aimed at helping astronauts deal with isolation and confinement could also have an impact on those back on Earth suffering from COVID-relat. . .
Keywords: mediaCoverage; proj--SIRIUS-earthgazing-newscoverage